Blue Carbon: Legal and Social Challenges for Coastal Communities in Indonesia - Tarigan, Vita Cita Emia (Universitas Sumatera Utara, 2025)
Blue carbon refers to the ability of coastal ecosystems such as mangroves, seagrass meadows and brackish lands to absorb and store large amounts of carbon, making them one of the most effective natural solutions in climate change mitigation. In Indonesia, which has a vast wealth of coastal ecosystems, blue carbon plays an important role not only in maintaining environmental balance, but also in supporting the lives and livelihoods of coastal communities. However, this great potential has not been fully utilized optimally due to various barriers, especially in legal and social aspects. This article aims to examine in depth the role of environmental law in supporting blue carbon management in Indonesia and its impact on coastal communities. The main focus of this study includes tenure issues (land rights and resource access), overlapping and disharmonized regulations between sectors, and low participation of local communities in the process of policy formulation and implementation. Using a normative approach and literature study, this research identifies the need for a clearer, more inclusive, and socially just legal framework for blue carbon ecosystem management. The results of this study are expected to contribute to the formation of policies that are more responsive to environmental sustainability while ensuring the protection of the rights of coastal communities as key stakeholders.